Performance evaluation of an all‐fiber ratiometric wavelength monitor system using edge filters based on sms fiber structures. Issue 7 (26th April 2013) - Hatta, Agus M.; Semenova, Y.; Farrell, G.
Abstract This article presents performance evaluation of the use of one or two edge filter(s) based on singlemode‐multimode‐singlemode (SMS) fiber structure on an all‐fiber ratiometric wavelength monitor system.Several aspects of noise, polarization‐dependent loss (PDL), and temperature‐dependent loss (TDL) that can influence the system's performance were investigated. It was demonstrated that the use of two SMS edge filters can improve the system's resolution and wavelength error when compared with the use of one edge filter. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1645–1649, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27619